Formation of phosphatidylethanol from endogenous phosphatidylcholines in animal tissues from pig, calf, and goat. (February 2018) - Luginbühl, Marc; Willem, Sytske; Schürch, Stefan; Weinmann, Wolfgang
Graphical abstract: Highlights: In vitro investigation of phosphatidylethanol formation in animal tissues. Simultaneous determination of phosphatidylethanol and phosphatidylcholine. Investigation of substrate availability and phosphatidylethanol formation. Abstract: In the presence of alcohol, phosphatidylcholine (PC) is transformed to the direct alcohol biomarker phosphatidylethanol (PEth). This reaction is catalyzed by the enzyme phospholipase D (PLD) and dependent on substrate availability. As recent methods have solely focused on the determination of PEth, information about the PC composition was generally missing. To address this issue and monitor PC (16:0/18:1 and 16:0/18:2) and PEth (16:0/18:1 and 16:0/18:2) simultaneously, a reversed phase LC–MS/MS method based on a C8 core–shell column, coupled to a Sciex 5500 QTrap instrument was developed. By application of polarity switching, at first, PC was measured in ESI positive SRM mode, while PEth was determined at a later stage in ESI negative SRM mode. The PEth method was validated for human blood samples to show its robustness and subsequently applied for the investigation of systematic in vitro PEth formation in animal tissue samples (brain, kidney, liver, and blood) from a pig, a calf, and a goat. Homogenized tissue was incubated at 37 °C with varying ethanol concentrations from 1 to 7 g/kg (determined by HS-GC-FID) for 5 h, whereby a sample was taken every 30 min. For all tissue samples, an increase in PEth was measurable. PEth concentrations formed in blood remained below the LLOQ, in agreement with literature. Data analysis of Michaelis–Menten kinetics and PC within the tissue provided a detailed insight about PEth formation, as the occurrence of PEth species can be linked to the observed PC composition. The results of this study show that PEth formation rates vary from tissue to tissue and among different species. Furthermore, new recommendations for PEth analysis are presented.